Targeted Antithrombotic Protein Micelles. (10th December 2014) - Kim, Wookhyun; Haller, Carolyn; Dai, Erbin; Wang, Xiowei; Hagemeyer, Christoph E.; Liu, David R.; Peter, Karlheinz; Chaikof, Elliot L.
Abstract Activated platelets provide a promising target for imaging inflammatory and thrombotic events along with site‐specific delivery of a variety of therapeutic agents. Multifunctional protein micelles bearing targeting and therapeutic proteins were now obtained by one‐pot transpeptidation using an evolved sortase A. Conjugation to the corona of a single‐chain antibody (scFv), which binds to the ligand‐induced binding site (LIBS) of activated GPIIb/IIIa receptors, enabled the efficient detection of thrombi. The inhibition of thrombus formation was subsequently accomplished by incorporating the catalytically active domain of thrombomodulin (TM) onto the micelle corona for the local generation of activated protein C, which inhibits the formation of thrombin. An effective strategy has been developed for the preparation of protein micelles that can be targeted to sites of activated platelets with broad potential for treatment of acute thrombotic events.